Literature Review Of Physical Exercise, Anxiety In Menopause Women - Maya Fadlilah; Chun Hoe Tan; Norhashima Abd Rashid (Fakultas Kesehatan IKesT Muhammadiyah Palembang, 2023)
Introduction: Menopause is defined as the cessation of monthly cycles for at least 12 months, and menopause syndrome, which includes symptoms of psychological illnesses including anxiety, is experienced by many women practically everywhere in the globe. Increased physical exercise is one non-pharmacological method for treating anxiety issues in menopausal women. According to several studies, exercising helps menopausal women's anxiety and depression levels. Method: The goal of this literature review is to examine physical exercise therapies against anxiety in menopausal women. This study technique uses literature review with secondary data gathered not from direct observation. Results: Based on the results of literature review analysis in 8 (eight) national and international journals showed that from the results of statistical tests of all physical exercise conducted in the study can reduce anxiety with a significance value of p < 0.05 which means physical exercise can reduce anxiety levels. Discussion: Physical exercise or exercise is very good for menopausal women because it can prevent or reduce the risk of cardiovascular disease, diabetes, osteoporosis, breast cancer, anxiety, alzaimer, and depression, regular exercise can be effective in reducing anxiety in menopausal women.